Preparation method of low-cost self-reinforced alumina thermal insulation material

By using waste alumina and lanthanum oxide to prepare alumina thermal insulation materials, the problems of reduced bauxite resources and insufficient performance of traditional pore-making agents are solved, and low-cost and high-performance alumina thermal insulation materials are achieved. , reduces production costs and improves environmental impact.

CN119143484APending Publication Date: 2024-12-17THE 52ND RES INST OF CHINA ORDNANCE IND GRP
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411267990.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-11
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

In the preparation of existing alumina thermal insulation materials, the reduction of high-alumina bauxite ore resources leads to an increase in production costs, and the traditional pore-making agent method has problems of environmental pollution and insufficient performance.

Method used

Use waste alumina as a substitute raw material for high alumina bauxite, and use lanthanum oxide as an additive to prepare low-cost and high-performance alumina thermal insulation materials through in-situ decomposition and low-dimensional structural effects. Specific steps include raw material pretreatment, mixing, forming and heat treatment, stabilizing lanthanum oxide through hydration treatment, imparting its pore-making function, and reducing the need for additional pore-making agents.

Benefits of technology

It has achieved the reduction of the preparation cost of alumina thermal insulation materials, reduced the demand for high-quality ore, solved the environmental pollution problem, and improved the comprehensive performance of the material, including porosity, mechanical properties and high-temperature thermal conductivity.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a preparation method of a low-cost self-reinforced alumina thermal insulation material, which comprises the following specific process flows: crushing waste alumina until the particle size is less than 75 microns (passing through a 200-mesh sieve), hydrating a lanthanum oxide additive at 95 DEG C for 2 hours, uniformly mixing 90-95% by mass of waste alumina powder and 5-10% by mass of the additive, and uniformly mixing the mixture with the additive to obtain the low-cost self-reinforced alumina thermal insulation material. And pressing the mixed powder into a green body under 10-30MPa, calcining the green body at 1300-1400 DEG C for 2-4 hours, and cooling along with a furnace to obtain the alumina thermal insulation material. A traditional pore-forming agent method is improved, no pollution is caused to the environment, internal pores are uniformly distributed, and the matrix bonding degree is higher. The prepared thermal insulation material is low in cost, outstanding in mechanical property and thermal insulation property and suitable for the field of high-temperature thermal insulation and service scenes with high performance requirements.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of heat insulation material preparation, and in particular relates to a method for preparing a low-cost self-reinforced alumina heat insulation material. Background Art

[0002] Alumina thermal insulation materials are the most widely used type of thermal insulation materials. They have the characteristics of wide raw material sources, stable high-temperature performance, and excellent comprehensive performance. They are currently mainly used in the field of high-temperature thermal insulation (>1200℃). Alumina thermal insulation materials are usually made from high-alumina bauxite or chemical alumina (which is expensive and mainly used to prepare products with high service environment requirements). However, with the large-scale mining over the years, the reserves of high-quality raw ore have gradually decreased, resulting in a gradual increase in its production cost. Therefore, it is urgent to find an alternative raw material to reduce the pressure of ore mining and save the preparation cost of alumina thermal insulation materials.

[0003] Compared with other preparation methods, the pore-forming agent method has the advantages of simple preparation process and low cost, and is one of the most commonly used methods for preparing alumina thermal insulation materials. However, it has two obvious disadvantages: one is the environmental problems caused by the pore-forming agent (some organic pore-forming agents); the other is the insufficient performance of the product (mainly due to poor bonding between the matrix resulting in poor mechanical properties). Therefore, it is necessary to improve and optimize the traditional pore-forming agent method to solve the environmental pollution problem and enhance the comprehensive performance of the product. Summary of the invention

[0004] The present invention aims to overcome the defects of the prior art, with the purpose of saving high-alumina bauxite resources, reducing the preparation cost of alumina thermal insulation materials, and solving the environmental problems and performance deficiencies of the traditional pore-forming agent method, and specifically provides a low-cost self-reinforced alumina thermal insulation material and a preparation method thereof. Specifically, the present invention uses waste alumina as a substitute raw material for high-alumina bauxite, lanthanum oxide as an additive (also a pore-forming agent), and produces a low-cost, high-performance alumina thermal insulation material through the synergistic effect of in-situ decomposition pore formation and low-dimensional structural effect.

[0005] To achieve the above object, the present invention provides the following solutions:

[0006] (1) Raw material pretreatment. Crushing the waste alumina to less than 75 μm (passing a 200-mesh sieve) and hydrating the lanthanum oxide additive;

[0007] (2) Mixing. Mix the waste alumina powder and additives evenly according to the mass fraction of 90% to 95% and 5% to 10%;

[0008] (3) Forming. The mixed powder is pressed into a green body at 10-30 MPa;

[0009] (4) Heat treatment: The green body is calcined at 1300-1400°C for 2-4 hours and cooled in the furnace to obtain an alumina thermal insulation material.

[0010] Further, the raw material pretreatment includes one or more of the waste alumina whose main component is the alumina phase, waste abrasives, waste furnace tubes, waste crucibles, waste thermocouple protection tubes, and waste electrical insulation substrates;

[0011] Furthermore, the hydration treatment parameters of the lanthanum oxide additive in the raw material pretreatment are lanthanum oxide and deionized water mixed in a ratio of 1:9 and treated in a water bath at 95° C. for 2 hours;

[0012] In fact, lanthanum oxide will react with water and carbon dioxide in the air at room temperature, which has a great impact on the forming process of the sample. Therefore, when lanthanum oxide is selected as an additive, the conventional practice is to heat treat it at more than 1200°C to make it fully dry. However, on the one hand, this method increases additional processes and energy consumption, and on the other hand, it does not really solve the impact of hydration of lanthanum oxide (hydration will still occur when lanthanum oxide is cooled to room temperature for use). Based on this, the present invention starts from the root, turns passive into active, and converts lanthanum oxide into more stable lanthanum hydroxide and lanthanum carbonate through simple artificial hydration treatment. Not only solves the stability problem of lanthanum oxide, but also gives the function of lanthanum oxide pore-forming agent (lanthanum hydroxide and lanthanum carbonate decompose in situ).

[0013] Furthermore, the additives in the mixture are additives that have been pre-treated by hydration and are calculated based on the mass of lanthanum oxide before treatment.

[0014] The present invention discloses the following technical effects:

[0015] First, the preparation cost is saved. The present invention uses alumina solid waste with a wide range of sources to replace high-alumina bauxite ore raw materials, which reduces the pressure on the demand for high-quality ores and provides a reference for the idea of ​​recycling industrial solid waste.

[0016] Secondly, the pore-forming agent method is improved. In order to solve the stability problem of lanthanum oxide, the present invention adopts a simple hydration pretreatment method to transform it into a more stable lanthanum hydroxide and lanthanum carbonate phase. Therefore, it is also endowed with a pore-forming function without the need to add additional pore-forming agents. The reaction equation for pore formation is 2La(OH) 3 =La 2 O 3 +3H 2 O.La 2 O 2 CO 3 =La 2 O 3 +CO 2 Compared with the traditional pore-forming agent method, it not only saves the cost of pore-forming agent, but also has no pollution to the environment.

[0017] Finally, the comprehensive performance is improved. The present invention uses lanthanum oxide as an additive to form plate-like lanthanum hexaaluminate (the reaction equation is La 2 O 3 +11Al 2 O 3 =2LaAl 11 O 18 ; Considering the hydration pretreatment of lanthanum oxide, the reaction equation should be 2La(OH) 3 +La 2 O 2 CO 3 +22Al 2 O 3 =4LaAl 11 O 18 +3H 2 O+CO 2 ) second phase, and the oriented growth of this special low-dimensional plate-like structure inhibits the high-temperature sintering shrinkage to a certain extent, thereby increasing its porosity (beneficial to thermal insulation performance). At the same time, the cross-linking of this special low-dimensional plate-like structure improves the bonding degree between particles, thereby improving its mechanical properties.

[0018] The performance indicators of the alumina thermal insulation material prepared by the present invention are as follows: the apparent porosity is 51.7% to 55.1%, and the volume density is 1.58 to 1.67 g / cm 3 The room temperature compressive strength is 17.5~30.6MPa, and the thermal conductivity at 25~1200℃ is 0.47~0.59W / (m·K). DETAILED DESCRIPTION

[0019] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0020] Example 1

[0021] (1) Raw material pretreatment. The waste alumina (waste alumina crucible) was crushed to less than 75 μm, and the lanthanum oxide additive and deionized water were mixed in a ratio of 1:9 and hydrated at 95 °C for 2 h;

[0022] (2) Mixing. Mix the waste alumina powder and additives evenly according to the mass fraction of 90% and 10%;

[0023] (3) Forming. The mixed powder is pressed into a green body at 10 MPa;

[0024] (4) Heat treatment: The green body is calcined at 1300°C for 2 hours and cooled in the furnace to obtain an alumina thermal insulation material.

[0025] After testing, the performance indicators of the alumina thermal insulation material prepared in this embodiment are as follows: the apparent porosity is 55.1%, the volume density is 1.59 g / cm 3 The room temperature compressive strength is 19.8MPa, and the thermal conductivity at 25-1200℃ is 0.47W / (m·K).

[0026] Example 2

[0027] (1) Raw material pretreatment. The waste alumina (waste alumina abrasive) was crushed to less than 75 μm, and the lanthanum oxide additive and deionized water were mixed in a ratio of 1:9 and hydrated at 95 °C for 2 h;

[0028] (2) Mixing. Mix the waste alumina powder and additives evenly according to the mass fraction of 95% and 5%;

[0029] (3) Forming. The mixed powder is pressed into a green body at 10 MPa;

[0030] (4) Heat treatment: The green body is calcined at 1300°C for 2 hours and cooled in the furnace to obtain an alumina thermal insulation material.

[0031] After testing, the performance indicators of the alumina thermal insulation material prepared in this embodiment are as follows: the apparent porosity is 53.8%, the volume density is 1.58g / cm 3 The room temperature compressive strength is 17.5MPa, and the thermal conductivity at 25-1200℃ is 0.51W / (m·K).

[0032] Example 3

[0033] (1) Raw material pretreatment. The waste alumina (waste alumina furnace tube) was crushed to less than 75 μm, and the lanthanum oxide additive and deionized water were mixed in a ratio of 1:9 and hydrated at 95°C for 2 h;

[0034] (2) Mixing. Mix the waste alumina powder and additives evenly according to the mass fraction of 92.5% and 7.5%;

[0035] (3) Forming. The mixed powder is pressed into a green body at 30 MPa;

[0036] (4) Heat treatment: The green body is calcined at 1350°C for 4 hours and cooled in the furnace to obtain an alumina thermal insulation material.

[0037] After testing, the performance indicators of the alumina thermal insulation material prepared in this embodiment are as follows: the apparent porosity is 53.1%, the volume density is 1.61 g / cm 3The room temperature compressive strength is 25.2MPa, and the thermal conductivity at 25-1200℃ is 0.49W / (m·K).

[0038] Example 4

[0039] (1) Raw material pretreatment. The waste alumina (waste thermocouple protection tube and waste alumina furnace tube mixed in a mass ratio of 1:1) was crushed to less than 75 μm, and the lanthanum oxide additive and deionized water were mixed in a ratio of 1:9 and hydrated at 95 °C for 2 h;

[0040] (2) Mixing. Mix the waste alumina powder and additives evenly according to the mass fraction of 92.5% and 7.5%;

[0041] (3) Forming. The mixed powder is pressed into a green body at 30 MPa;

[0042] (4) Heat treatment: The green body is calcined at 1400°C for 2 hours and cooled in the furnace to obtain an alumina thermal insulation material.

[0043] After testing, the performance indicators of the alumina thermal insulation material prepared in this embodiment are as follows: the apparent porosity is 52.6%, the volume density is 1.63g / cm 3 The room temperature compressive strength is 27.8MPa, and the thermal conductivity at 25-1200℃ is 0.53W / (m·K).

[0044] Example 5

[0045] (1) Raw material pretreatment. The waste alumina (waste electrical insulation substrate) was crushed to less than 75 μm, and the lanthanum oxide additive and deionized water were mixed in a ratio of 1:9 and hydrated at 95 °C for 2 h;

[0046] (2) Mixing. Mix the waste alumina powder and additives evenly according to the mass fraction of 90% and 10%;

[0047] (3) Forming. The mixed powder is pressed into a green body at 20 MPa;

[0048] (4) Heat treatment: The green body is calcined at 1400°C for 4 hours and cooled in the furnace to obtain an alumina thermal insulation material.

[0049] After testing, the performance indicators of the alumina thermal insulation material prepared in this embodiment are as follows: the apparent porosity is 53.3%, the volume density is 1.67g / cm 3 The room temperature compressive strength is 30.6MPa, and the thermal conductivity at 25-1200℃ is 0.51W / (m·K).

[0050] Example 6

[0051] (1) Raw material pretreatment. Waste aluminum oxide (waste electrical insulation substrate and waste abrasive mixed in a mass ratio of 1:1) was crushed to less than 75 μm, and lanthanum oxide additive and deionized water were mixed in a ratio of 1:9 and hydrated at 95 °C for 2 h;

[0052] (2) Mixing. Mix the waste alumina powder and additives evenly according to the mass fraction of 95% and 5%;

[0053] (3) Forming. The mixed powder is pressed into a green body at 30 MPa;

[0054] (4) Heat treatment: The green body is calcined at 1400°C for 4 hours and cooled in the furnace to obtain an alumina thermal insulation material.

[0055] After testing, the performance indicators of the alumina thermal insulation material prepared in this embodiment are as follows: the apparent porosity is 51.7%, the volume density is 1.62g / cm 3 The room temperature compressive strength is 28.4MPa, and the thermal conductivity at 25-1200℃ is 0.59W / (m·K).

[0056] The overall process of the above embodiments remains consistent, and only the technical details such as the source of raw materials, the proportion of additives and the calcination temperature are slightly changed. For example, compared with Example 1, Example 2: although the aluminum source is different (waste alumina crucible and waste alumina abrasive), it will not have a significant effect on the performance after standard crushing and screening; the amount of lanthanum oxide additive added in Example 2 is reduced from 10% to 5%, which is beneficial to saving material costs, but it also leads to a reduction in the flaky lanthanum aluminate reinforcement phase, and the final performance is that the apparent porosity, thermal insulation performance and strength are slightly lower than those in Example 1. For example, compared with Example 3 and Example 4: the aluminum source is different, but it has no effect (the reason is the same as above); the calcination temperature of Example 4 is increased from 1350 to 1400℃, the sample interface reaction is more sufficient, the reinforcement phase is more closely combined with the porous matrix, and finally it is manifested as higher strength. For example, Example 5 and Example 6 are similar to Example 1 and Example 2, and Example 5 with a higher content of lanthanum oxide additives shows higher apparent porosity and strength, and lower thermal conductivity. Therefore, when the present invention is implemented, the technical details can be adjusted according to the relevant needs of cost and performance to obtain an alumina thermal insulation product with a more ideal structure and better comprehensive performance.

[0057] In addition, the above embodiments are intended to illustrate the technical content of the present invention rather than to limit the implementation methods of the present invention. Any technical extension or re-creation made according to the present invention is within the protection scope of the present invention.

Claims

1. A method for preparing a low-cost self-reinforced alumina thermal insulation material, characterized in that: The following steps are involved: (1) Raw material pretreatment The waste alumina is crushed to less than 75 μm, and the additive lanthanum oxide is hydrated; (2) Mixing Mix 90% to 95% by mass of waste alumina powder and 5% to 10% by mass of additive lanthanum oxide uniformly; (3) Forming Pressing the mixed powder into a green compact at 10-30 MPa; (4) Heat treatment The green body is calcined at 1300-1400° C. for 2-4 hours and cooled in the furnace to obtain an alumina thermal insulation material.

2. The preparation method according to claim 1, characterized in that: The waste aluminum oxide in the raw material pretreatment of step (1) is one or more of waste abrasives, waste furnace tubes, waste crucibles, waste thermocouple protection tubes or waste electrical insulating substrates whose main component is aluminum oxide phase.

3. The preparation method according to claim 1, characterized in that: The hydration treatment parameters of the additive lanthanum oxide in the raw material pretreatment of step (1) are as follows: the mass ratio of lanthanum oxide to deionized water is 1:9, and the treatment is carried out in a water bath at 95° C. for 2 h.

4. The preparation method according to claim 1, characterized in that: The lanthanum oxide additive in the mixing step (2) is an additive that has been pre-treated by hydration, and is calculated based on the mass of the lanthanum oxide before the treatment.

Citation Information

Patent Citations

  • Method for preparing lanthanum aluminate powder efficiently

    CN103112881A

  • Large-grain low-thermal-conductivity magnesite clinker and preparation method thereof

    CN115974563A

  • Yttrium oxide ceramic crucible for titanium alloy smelting and preparation method thereof

    CN116675536A

  • Process for Producing High Porosity Boehmite Aluminas

    US20080193369A1